Comunicação pública e marketing político na gestão pública municipal - Silva, Élida Raquel Mercês da (2012)
Based on the definitions of Public Communication, Political Marketing, Public Interest Information and Communication as a Tool of Governance, the study notes the use of the news section of the websites of the City Christmas and Mossoro, Rio Grande do Norte, in regard to strengthening citizenship and encouraging participatory management, from the characterization of materials like pieces of Political Marketing and Public Communication. Data collection in qualitative research was conducted from August to September 2011 and content analysis showed that the appropriation of public property for personal use is a reality, despite legal requirements to the detriment of strategic communication and governance for results from the dissemination of information of public interest and the establishment of a communication channel between State Government and Society. Elements of this study suggest the need for further research to deepen the discussion